#TITLE_ALTERNATIVE# - PRAYUDI (NIM : 12208069), IHSAN
Surfactant flooding is one of Enhance Oil Recovery technique that can increase oil recovery by decreased residual oil saturation thus increase moveable oil saturation in reservoir. However, using surfactant flooding usually has high cost. Because of that fact, economical value of using surfactant flooding need to be determinded. Recovery factor is one of factor that influence economical value of a project. The higher the recovery factor because the project, the better the economical value of that project. So, before start a project, we must determine the recovery factor of the project. This paper contains study about simulation of oil recovery factor prediction of surfactant flooding four-spot pattern by using eclipse as simulator. The reservoir model is built with one production well and three injection well. The reservoir model is simulated with sensitivity of surfactant consentration, residual oil saturation, and surfactant injection time. The result of the study is obtained a linear equation that can predict oil recovery factor of surfactant flooding four Ã‚Â–spot pattern using oil recovery factor value before surfactant flooding and residual oil saturation as variables. This paper also compares oil recovery factor from equation that predict oil recovery factor using surfactant flooding four-spot pattern, five-spot pattern, and seven-spot pattern. The conclusion of comparison is that four-spot injection produces the smallest oil recovery factor and seven-spot injection produces the largest oil recovery factor.